EZH2 and NF-κB: A context-dependent crosstalk and transcriptional regulation in cancer. (28th April 2023) - Kaur, Parminder; Verma, Shiv; Kushwaha, Prem Prakash; Gupta, Sanjay
Abstract: Epigenetic modifications regulate critical biological processes that play a pivotal role in the pathogenesis of cancer. Enhancer of Zeste Homolog 2 (EZH2), a subunit of the Polycomb-Repressive Complex 2, catalyzes trimethylation of histone H3 on Lys 27 (H3K27) involved in gene silencing. EZH2 is amplified in human cancers and has roles in regulating several cellular processes, including survival, proliferation, invasion, and self-renewal. Though EZH2 is responsible for gene silencing through its canonical role, it also regulates the transcription of several genes promoting carcinogenesis via its non-canonical role. Constitutive activation of Nuclear Factor- kappa B (NF-κB) plays a crucial role in the development and progression of human malignancies. NF-κB is essential for regulating innate and adaptive immune responses and is one of the most important molecules that increases survival during carcinogenesis. Given the evidence that increased survival and proliferation are essential for tumor development and their association with epigenetic modifications, it seems plausible that EZH2 and NF-κB crosstalk may promote cancer progression. In this review, we expand on how EZH2 and NF-κB regulate cellular responses during cancer and their crosstalk of the canonical and non-canonical roles in a context-dependent manner. Highlights: EZH2 catalyzes trimethylation of histone H3 on Lys 27 involved in gene silencing. NF-κB plays a crucial role in the development and progression of human malignancies. A crosstalk exists between EZH2 and NF-κB in a contextual dependent manner. EZH2-NF-κB crosstalk may promote cancer progression.